Translation Techniques and Acceptability of Onomatopoeia in Herge’s The Adventure of Tintin Comic - Inas Haninisa; Dyah Raina Purwaningsih; Raden Pujo Handoyo (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2020)
This research is aimed to analyze the types of onomatopoeia, techniques of translation as well as the acceptability aspect of the translated onomatopoeia in The Adventure of Tintin comic in order to compare how English and Indonesian in naming the sound of something and know how translation techniques can affect the quality of translation products. This research used descriptive qualitative method and total sampling. This research primarily applied the theory of onomatopoeia especially the types of onomatopoeia from Thomas and Clara (2004:4), Molina and Albir’s (2002: 509) theory of translation techniques and Translation Quality Assessment (TQA) proposed by Nababan (2012: 44) which focused on acceptability aspect. The result shows that there are 121 data found in 21 comic series of Tintin. There are four types of onomatopoeia which are call of animals (19%), sound made by humans (17.3%), sound of nature (8.3%) and miscellaneous sound (55.4%). Meanwhile, techniques that are used by the translator are only five techniques. The techniques consist of adaptation (5%), borrowing (34.7%), discursive creation (19%), established equivalent (37.2%), and reduction (4.1%). At last, the translated onomatopoeia in Tintin comic are predominantly acceptable which has a total 82% of onomatopoeia, 15% belong to less acceptable, and 3% belong to unacceptable